IDENTIFIKASI FAKTOR YANG MEMPENGARUHI PENGEMBANGAN DAYA TARIK WISATA PANTAI CEMARASEWU DI DAERAH ISTIMEWA YOGYAKARTA - Achmad Andi Rif'an; M. Rizky Ferdinandsyah; Aristy W. Ramadhani; Defva S. Agatha; Fidelia A. Bryliandita; M. Fajar Dinar (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
Cemara Sewu Beach is a beach located in the southern coastal area of Java Island or more precisely how many in Bantul Regency, DIY Province on the South side. The purpose of this study is to formulate about the development of Cemara Sewu Beach in a competitive situation with other tourist attractions adjacent to this beach. . The results of this study are strategies that must be carried out by the government as managers and related agencies in the management of Cemara Sewu beach, including optimizing the promotion of Cemara Sewu Beach in order to maintain the stability of the number of tourists by considering the side of tourist attraction, making certain events that can attract tourists and adding and optimizing all existing and needed facilities in the area.